Deregulated glutamate to pro-collagen conversion is associated with adverse outcome in lung cancer and may be targeted by renin-angiotensin-aldosterone system (RAS) inhibition. (September 2021) - Kocher, Florian; Tymoszuk, Piotr; Amann, Arno; Sprung, Susanne; Salcher, Stefan; Daum, Sophia; Haybaeck, Johannes; Rinnerthaler, Gabriel; Huemer, Florian; Kauffmann-Guerrero, Diego; Tufman, Amanda; Seeber, Andreas; et al.
Graphical abstract: Highlights: Most genes involved in collagen metabolism are upregulated in NSCLC. High expression of those genes is associated with poor outcome. In vitro RAS inhibitors led to a dose dependent decrease of collagen deposition. RAS inhibitor intake was associated with improved survival in a large NSCLC cohort. Our results point towards collagen biosynthesis as a promising target in NSCLC. Abstract: Background: The tumor-microenvironment (TME) represents an attractive therapeutic target in NSCLC and plays an important role for efficacy of cancer therapeutics. We hypothesized that upregulation of collagen synthesis might be associated with adverse outcome in NSCLC. Literature evidence suggests that renin-angiotensin system inhibitors (RASi) decrease collagen deposition. Therefore, we aimed to explore the prognostic role of RASi intake and their influence on the TME in NSCLC. Methods: Four publicly available datasets were used to evaluate the impact of key enzymes involved in collagen biosynthesis. To investigate the influence of RASi intake on the TME and prognosis we evaluated a cohort of metastatic NSCLC patients and performed histopathological characterization of the TME. A three-dimensional microtissue in vitro model was developed to define the impact of RASi on collagen synthesis. Results: Expression of three genes of the collagen synthesis pathway, ALDH18A1, PLOD2 and P4HA1, was upregulated in NSCLC compared to normal lung tissue and linked to shortened overall survival in all investigated cohorts. Together, these genes formed a 'Collagen Signature' which represents an independent unfavourable prognostic factor in two NSCLC cohorts and was linked to alterations of the extracellular matrix deposition and cell cycle pathways. In the cohort of metastatic NSCLC, RASi intake was linked to improved overall response rate and survival. Exploratory in vitro experiments revealed that RASi led to a dose dependent reduction of collagen deposition and degradation of three-dimensional lung cancer cell spheroids. Conclusion: We demonstrate that collagen synthesis is a key upregulated process in the NSCLC TME and its transcriptional readout, the three gene Collagen Signature is independently associated with poor outcome. Pharmacological targeting of this pathways e.g. by RASi bears potential of improving outcome in NSCLC.